ANALYZING FACTORS THAT DRIVE EMPLOYEE PRODUCTIVITY ( CASE STUDY OF PT. BANK SULUTGO MAIN OFFICE MANADO ) - Porawouw, Regita .; Pangemanan, Sifrid S.; Tumbuan, Willem J.F.A (FEB Universitas Sam Ratulangi Manado, 2017)
Abstract: Employee is an important aspect that determines the success of a company to become more competitive in global business environment. This research aims to analyze the factors that drive employee productivity in main office of PT. Bank SulutGo Manado. This is a quantitative descriptive research and used factor analysis as the measurement tool. The sample size of this research is 100 respondents who worked in PT. Bank SulutGo Main Office Manado. Convenience sampling was used by collecting data through questionnaire. The result revealed that There are three most dominant out of twenty factors. There are Manager Attitude, Leadership, and Role Congruity. These three factors are most dominant from twenty factors that has been tested, which are Experience, Employee Satisfaction, Work Environment, Work Processes, Employee Welfare, Employee Performance, Motivation, Salary, Incentive, Rewards, Manager Attitude, Supervisor Support, Leadership, Skill, Career Development, Role Congruity, Work Discipline, Job Aids, Performance Feedback, and Goal Setting) of employee productivity in PT. Bank SulutGo, which are Manager Attitude, Leadership and Role Congruity. Based on communality test, the highest value is Manager Attitude, followed by Leadership and Role Congruity.Â Keywords: employee productivity, factor analysis